Material Safety And Data Sheet:A Review - Modh, Mayur (International Journal of Pharmaceutical & Biological Archive, 2011)
ABSTRATMaterial Safety Data Sheets (MSDSs) are essential sources of information regarding health risks from exposure to toxic chemicals. We analyzed the reproductive health hazard descriptions on nearly 700 MSDSs for lead- or ethylene glycol ether-containing products submitted by central Massachusetts firms to the Department of Environmental Protection under provisions of the Massachusetts Right-to-Know Law. Over 60% of the MSDSs made no mention whatsoever of effects on the reproductive system. Those that did were much more likely to address developmental risks than male reproductive effects. The MSDSs from firms employing 100 or more workers mentioned reproductive system effects more frequently than those from smaller companies. While the informativeness of the health hazard descriptions increased over time, 53% of the MSDSs prepared after promulgation of the OSHA Hazard Communication Standard still contained no information on reproductive risks. Key Words: Material safety Data Sheets, Environmental Protection, OSHA Hazard Communication standards.